Chronic granulomatous disease presenting as an oculomucocutaneous syndrome mimicking Behcet's syndrome - FEIGHERY, CONLETH FRANCIS; GRIFFIN, MAIREAD; KELLEHER, DERMOT P; MCCANN, SHAUN (BMJ, 1986)
A female patient who presented for the first time at the age of 19 with oculomucocutaneous syndrome was found to have an absolute deficiency of neutrophil peroxide production. Neutrophil peroxide production as measured by chemiluminescence was zero on stimulation with opsonized zymosan. Direct membrane stimulation with FMLP and calcium ionophore also failed to elicit peroxide production. The diagnosis of chronic granulomatous disease should be considered in young patients with oculomucocutaneous syndrome.
PUBLISHED
Keywords: Clinical Medicine